2005
DOI: 10.1111/j.1365-3156.2004.01377.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the health status of young AIDS and other orphans in Kampala, Uganda

Abstract: Summary The huge number of human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) orphans is an important feature of the epidemic in sub‐Saharan Africa. There are few and conflicting data on the effects of being orphaned on health and nutrition in the highly affected HIV endemic areas of Africa. This study reports findings from a cross‐sectional survey on associations between orphan status and health and nutrition parameters in young children of urban Uganda. A high prevalence of orphans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
2
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 23 publications
(27 reference statements)
3
27
2
4
Order By: Relevance
“…8,14 The findings of our study are in contrast to the Mumbai study which found that despite the death of one or both parent(s), the children were being adequately taken care of by the extended family caregivers. 9 The orphans more frequently presented with severe immunosuppression and had a higher prevalence of opportunistic infections.…”
Section: Discussioncontrasting
confidence: 84%
“…8,14 The findings of our study are in contrast to the Mumbai study which found that despite the death of one or both parent(s), the children were being adequately taken care of by the extended family caregivers. 9 The orphans more frequently presented with severe immunosuppression and had a higher prevalence of opportunistic infections.…”
Section: Discussioncontrasting
confidence: 84%
“…Two differences between northern and southern Malawi are that the south is much poorer and has matrilineal culture. Sarker et al (2000) have also reported in their study from Kampala, Uganda that the health and nutrition status of orphans were similar to non-orphaned children.…”
Section: Discussionmentioning
confidence: 75%
“…Orphans have lower school attendance, lower school completion rates, and/or are less likely than non-orphans to be at the age-appropriate grade level (Bicego, Rutstein, & Johnson, 2003;Makame et al, 2002;Monasch & Boerma, 2004;Nyambedha et al, 2003b;Nyamukapa & Gregson, 2005). Although mixed results about physical health and health care access have been reported among orphans as compared with non-orphans (Crampin et al, 2003;Lindblade, Odhiambo, Rosen, & DeCock, 2003;Masmas et al, 2004;Nyambedha et al, 2003a;Nyambedha et al, 2003b;Sarker, Neckermann, & Muller, 2005), psychological problems have been consistently observed among orphans (Atwine, Cantor-Graae, & Bajunirwe, 2005;Cluver & Gardner, 2006;Makame et al, 2002;Pelton & Forehand, 2005). Orphans have markedly increased internalizing problems and higher levels of anxiety, depression, anger, and depressive disorders, as compared with their counterparts (Atwine et al, 2005;Makame et al, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…A substantial literature exploring the impact of orphanhood on the well-being of children has emerged in the past few years. A wide range of topics has been discussed in the literature, including living situation, physical health, schooling, bereavement process, and psychological well-being (Makame, Ani, & Grantham-McGregor, 2002;Masmas et al, 2004;Monasch & Boerma, 2004;Safman, 2004;Nyamukapa & Gregson, 2005;Sarker, Neckermann, & Muller, 2005;).…”
Section: Introductionmentioning
confidence: 99%